2008
DOI: 10.1039/b813414f
|View full text |Cite
|
Sign up to set email alerts
|

Modular synthesis of multivalent glycoarchitectures and their unique selectin binding behavior

Abstract: Hyperbranched polyglycerols (HPGs) are ideal scaffolds for the multivalent presentation of saccharides, due to their biocompatible, carbohydrate-like properties; here, we report the conjugation of galactosesugar moieties to HPG, and the multivalent effect of these constructs on selectin binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 33 publications
0
73
0
2
Order By: Relevance
“…Tethering and rolling of leukocytes mediated by binding to their respective carbohydrate ligands on endothelial cells prime leukocytes for firm adhesion and subsequent extravasation. In a recent study, we showed that galactose functionalized polyglycerol dendrimers were able to bind the three selectins, but with low affinity (21). In contrast sulfation of the carbohydrate tuned the selectivity of the polymer toward L-and P-selectin and IC 50 values decreased by (B) Reduction of neutrophil extravasation, as measured by specific elastase activity from ear homogenates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tethering and rolling of leukocytes mediated by binding to their respective carbohydrate ligands on endothelial cells prime leukocytes for firm adhesion and subsequent extravasation. In a recent study, we showed that galactose functionalized polyglycerol dendrimers were able to bind the three selectins, but with low affinity (21). In contrast sulfation of the carbohydrate tuned the selectivity of the polymer toward L-and P-selectin and IC 50 values decreased by (B) Reduction of neutrophil extravasation, as measured by specific elastase activity from ear homogenates.…”
Section: Discussionmentioning
confidence: 99%
“…S1) that allows the determination of IC 50 values for inhibitory compounds over a large concentration range (pM-mM) (20,21). Initially, we analyzed the selectin specificity of dPGS.…”
mentioning
confidence: 99%
“…45) for the inhibition of L-and P-selectins, a general class of receptors which displays a selective adhesion and includes a lectin-like domain. [210] Two structures were compared, namely, free PG-galactose (R ¼ H in Fig. 44) and PG-sulfated galactose (R ¼ SO 3 Na).…”
Section: Negatively Charged Derivatesmentioning
confidence: 99%
“…To provide valuable information about multivalent binding, we synthesized hyperbranched polyglycerol cores with different functionalizations, chain lengths, and degrees of carbohydrate shell functionalities. Recently, [22] we reported the synthesis of galactose neoglycopolymers by a Cu I -catalyzed Huisgen 1,3-dipolar cycloaddition process. Our approach involved the grafting of sugar azides onto a polyalkyne clickable scaffold that was successfully used for selectin inhibition studies.…”
Section: Introductionmentioning
confidence: 99%
“…[26a] The functionalization of hPG and Man derivatives were achieved by employing previously reported experimental conditions. Initially, a fraction of free hydroxyl groups on the hPG core (M n = 5 kDa) were converted either to propargyl ethers [22] with controlled and varied degrees of functionalization 1-3 (15, 50, and 90 %), or the hydroxyl groups were transformed into azides [27] (4-6) with the same functionalities as mentioned above (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%